Prevalence of anxious and depressive symptoms in college students of a public institution - Márcia Astrês Fernandes; Francisca Emanuelle Rocha Vieira; Joyce Soares e Silva; Fernanda Valéria Silva Dantas Avelino; José Diego Marques Santos (Revista Brasileira de Enfermagem)
ABSTRACT Objective: Identify the prevalence of anxious and depressive symptoms and their correlations with sociodemographic and occupational characteristics in university students. Method: This is census, cross-sectional and analytical study, developed with nursing students of a federal public university in the Northeast of Brazil in the months of September and October 2016. 205 university students of all the periods of the course attended the study. Beck’s inventories for anxiety and depression were applied. Results: Most of the participants were female, single, native of the state capital and living with his parents. The prevalence of depression was 30.2% and of anxiety, 62.9%. Association between the level of depressive symptoms, work, sex and leisure was identified. Conclusion: The prevalence of symptoms of anxiety and depression was quite expressive, lacking, thus, more attention to the promotion of mental health of nursing students.